KPP Pratama Makassar Barat Assesses The Impact of Tax Sanctions, Fiskus Services, and The Taxpayer's Environment. - N. Nasrullah (Manunggal Halim Jaya, 2022)
This study aims to analyze the effect of tax sanctions, tax authorities, level of understanding, awareness, and the environment of taxpayers on individual taxpayer compliance at KPP Pratama Makassar Barat. This study uses primary and secondary data. Primary data was obtained through the answers of each respondent and secondary data was obtained from KPP Pratama Makassar Barat related to the number of registered individual taxpayers, taxpayers who are subject to SPT, and the number of taxpayers who report SPT. The sample in this study is 100 individual taxpayers who are registered at KPP Pratama Makassar Barat. Data were analyzed using the SPSS statistical program. The results of this study indicate that simultaneously all independent variables have a positive and significant effect on individual taxpayer compliance. Then based on partial testing, only the level of understanding variable (X3) and the awareness variable (X4) do not significantly influence individual taxpayer compliance (Y) at KPP Pratama Makassar Barat.